Beach sand: knowing pathogen levels, their potential to harm human health and preventive actions / Nur Azlin Atikah Mohd Nasir ... [et al.] - Mohd Nasir, Nur Azlin Atikah; Ramli, Nurul Annisa; Fadzil, Nur Farhan Natasha; Muhammad Fauzi, Nursuhaila; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
For fun activities, beaches are essential. This is especially true in northern countries, where people spend more time on the beaches than in the water because the water is cold. Millions of people from around the world visit beaches yearly for fun. The picture-perfect look of these beach spots, on the other hand, can hide health risks. Pathogens found in beach sand are a significant cause for worry. Microorganisms like bacteria, viruses, and parasites that can make people sick are called pathogens. In beach sand, they can harm people's and the earth’s health. Understanding the pathogen levels in beach sand is critical for various reasons. First and foremost, it aids in the protection of public health. Sand contamination can cause various health concerns, including gastrointestinal infections, skin difficulties, and respiratory ailments. Identifying and measuring viruses in beach sand can assist authorities and beachgoers in making educated judgements about whether swimming and playing on the sand is safe. Furthermore, understanding pathogen levels in beach sand is critical for coastal ecosystem protection.